Ethnography of community governance: A case of COVID-19 response of an urban slum in Bangladesh - Zaman, Shahaduz; Hossain, Faruq; Matin, Imran (Oxford Academic, 2024)
This article was published in The Community Development Journal [©2023 Rights managed by Oxford Academic ] and the definite version is available at: https://doi.org/10.1093/cdj/bsac006 The Article's website is https://academic.oup.com/cdj/article/58/2/247/6549892